Analysis of Mathematical Connection Ability to Students' Learning Motivation in Advanced Mathematics Courses - Herisa Hardiyanti Sholeha; Pratiwi Pujiastuti; Asih Mardati (STAI Hubbulwathan Duri, 2022)
This study aims to learn how the students' mathematical connections are and discover the influence of the mathematical connections on students’ motivation in advanced mathematics learning. The population of this research is the second-semester students of a state university in Yogyakarta, and the subject is 84 students. The instrument used was the question sheets on the mathematical connection ability on advanced mathematics materials, the questionnaire instrument, and the interview guidelines related to learning motivation. The data analysis used was the descriptive statistics analysis. The results of this study indicate that (1) the students’ mathematical connection ability was low, (2) the influence of connection abilities on motivation was very low.